ANALISIS PENGGUNAAN MEDIA QUIZIZZ TERHADAP PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS 5 SDN PADEMAWU TIMUR 5 - Ach Zubairi Malik; Wahdian , Agus; Sama' (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In the digital era, innovation in teaching methods is essential to increase student learning interest. One effective solution is the use of technology-based media, such as Quizizz, which offers interactive and engaging learning experiences. At SDN Pademawu Timur 5, conventional teaching methods still dominate, leading to low student participation and interest in Pancasila Education. This research aims to examine the influence of using Quizizz on enhancing the learning interest of 5th-grade students in Pancasila Education. Employing a qualitative approach and a case study method, data were collected through observation, interviews, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawing. The research subjects consisted of 5th-grade students and Pancasila Education teachers, with data validity strengthened through triangulation techniques. The findings reveal that the implementation of Quizizz positively contributes to increasing students' learning interest. Students became more enthusiastic and active compared to conventional lecture methods. Quizizz’s gamification features, such as ranking systems and instant feedback, further boosted student motivation. However, some challenges were identified, including limited device availability and student adaptation to technology. To overcome these obstacles, the school provided additional devices as well as capacity-building programs for educators and learners to maximize the effectiveness of Quizizz utilization. Overall, the use of Quizizz has proven effective in increasing student interest in Pancasila Education. The results of this research can function as a valuable reference for educational institutions in incorporating technology into the learning process to improve the overall quality of education.